The claustrum in review - Mathur, Brian N. (Frontiers in Systems Neuroscience, 2014)
The claustrum is among the most enigmatic of all prominent mammalian brain structures. Since the 19th century, a wealth of data has amassed on this forebrain nucleus. However, much of this data is disparate and contentious; conflicting views regarding the claustrum’s structural definitions and possible functions abound. This review synthesizes historical and recent claustrum studies with the purpose of formulating an acceptable description of its structural properties. Integrating extant anatomical and functional literature with theorized functions of the claustrum, new visions of how this structure may be contributing to cognition and action are discussed.